U-IMD: the first Unified European registry for inherited metabolic diseases - Opladen, Thomas; Gleich, Florian; Kozich, Viktor; Scarpa, Maurizio; Martinelli, Diego; Schaefer, Franz; Jeltsch, Kathrin; Juliá-Palacios, Natalia; García-Cazorla, Ángels; Dionisi-Vici, Carlo; Kölker, Stefan (Orphanet journal of rare diseases, 2021)
Following the broad application of new analytical methods, more and more pathophysiological processes in previously unknown diseases have been elucidated. The spectrum of clinical presentation of rare inherited metabolic diseases (IMDs) is broad and ranges from single organ involvement to multisystemic diseases. With the aim of overcoming the limited knowledge about the natural course, current diagnostic and therapeutic approaches, the project has established the first unified patient registry for IMDs that fully meets the requirements of the European Infrastructure for Rare Diseases (ERDRI).
Gesehen am 20.02.2023